Harmonization of International Instruments and National Regulations for the Protection of Indonesian Migrant Workers: Achieving Global Compliance and Comprehensive Protection - Sri Mulyani; Dikha Anugrah (Fakultas Hukum Universitas Islam Indonesia, 2025)
The cross-border mobility of Indonesian labor has become a global phenomenon that significantly contributes to the national foreign exchange, yet simultaneously poses a substantial risk of human rights violations in the absence of adequate legal protection. This article examines the disharmony between international legal instruments and national regulations in the context of protecting Indonesian migrant workers. Utilizing a normative juridical approach and qualitative method, the study finds that Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers (PPMI Law) is not fully aligned with the principles enshrined in the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICRMW) and other relevant international conventions. Such inconsistencies not only weaken legal protection at all stages of the migration cycle but also give rise to serious legal implications for the State as the guarantor of its citizens' rights. This research recommends legal harmonization strategies and institutional strengthening to ensure comprehensive and equitable fulfillment of migrant workers' rights.